Pengaruh Rasio Likuiditas dan Rasio Aktivitas Terhadap Profitabilitas Pada PT. Surya Toto Indonesia, Tbk - Melly Sukma Dewi Ratu Mutiara; Alwi Alwi; Wulandari Wulandari (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to analyze the influence of liquidity ratio and activity ratio on profitability in PT. Surya Toto Indonesia, Tbk. Liquidity ratio is measured using Current Ratio (CR) and Quick Ratio (QR), while activity ratio is measured using Total Asset Turnover (TATO) and Inventory Turnover (ITO). The research method used is a quantitative method with a multiple linear regression approach. The data used in this study is secondary data obtained from the financial statements of PT. Surya Toto Indonesia, Tbk during the 2018-2022 period. The results show that the liquidity ratio and activity ratio have a significant influence on profitability as measured by Return on Assets (ROA). Current Ratio (CR) and Total Asset Turnover (TATO) have a positive and significant effect on profitability, while Quick Ratio (QR) and Inventory Turnover (ITO) have a negative but insignificant effect. These findings indicate that companies should pay attention to liquidity management and their operational activities to increase profitability.